2018
DOI: 10.3389/fgene.2018.00358
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-Wide Analyses Identify Two Novel Associations With Recurrent Stroke in the Vitamin Intervention for Stroke Prevention Clinical Trial

Abstract: DNA methylation, a well-characterized epigenetic modification that is influenced by both environment and genetic variation, has previously been implicated in a number of complex diseases, including cardiovascular disease and stroke. The goal of this study was to evaluate epigenome-wide associations with recurrent stroke and the folate one-carbon metabolism-related trait, plasma homocysteine (hcy). Differential methylation analyses were performed on 473,864 autosomal CpG loci, using Illumina HumanMethylation 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…As previously described, Illumina Infinium HumanMethylation450K BeadChip microarrays (Illumina, Inc., San Diego, CA, United States) were used per the manufacturer’s protocol to determine the degree of methylation (β values) for 485,512 methylation loci [ 11 ]. Quality control and quantile normalization was performed, resulting in 473,864 autosomal methylation CpG loci [ 12 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…As previously described, Illumina Infinium HumanMethylation450K BeadChip microarrays (Illumina, Inc., San Diego, CA, United States) were used per the manufacturer’s protocol to determine the degree of methylation (β values) for 485,512 methylation loci [ 11 ]. Quality control and quantile normalization was performed, resulting in 473,864 autosomal methylation CpG loci [ 12 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…With regards to arterial thrombotic diseases, EWASs have identified several CpGs that are differentially methylated in cases with myocardial infarction (MI) or ischemic stroke compared with controls. 11 12 13 14 A large EWAS also identified CpGs showing differential methylation in relation to age-independent cardiovascular risk factors. 15 A methylation risk score, created based on these differentially methylated CpGs, was significantly associated with incident cardiovascular events in the Framingham offspring study, and this association was independent of age, sex, and classical vascular risk factors.…”
Section: Introductionmentioning
confidence: 97%
“…8,9 In addition to genetic variants, there is increasing evidence for the involvement of epigenetic mechanisms, such as DNA methylation, in many human diseases, 10 and those caused by arterial or venous thrombosis are no exception. [11][12][13][14] Over the last few years, technological advances have made it possible to perform so-called epigenome-wide association studies (EWASs) by the use of bead arrays that allow for genome-wide mapping of DNA methylation at a large number of cytosine-phosphate-guanine (CpG) dinucleotide sites. With regards to arterial thrombotic diseases, EWASs have identified several CpGs that are differentially methylated in cases with myocardial infarction (MI) or ischemic stroke compared with controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that those who have hyperhomocysteinemia (Hhcy) have a higher risk of the development of AIS, and Hhcy is correlated with poor prognosis in AIS patients ( Davis Armstrong et al, 2018 ; Zaric et al, 2019 ). Besides, the increased risk of cardiovascular disease could also be partially attributed to Hhcy ( Borowczyk et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%